Liquefaction-Induced Horizontal Displacements from the Canterbury Earthquake Sequence in New Zealand Measured from Remote Sensing Techniques. Issue 4 (November 2017) - Rathje, Ellen M.; Secara, Sorin S.; Martin, Jonathan G.; van Ballegooy, Sjoerd; Russell, James
Using satellite image pairs from the 2010–2011 Canterbury Earthquake Sequence (CES) in New Zealand, optical image correlation is used to measure horizontal displacements due to liquefaction-induced lateral spreading. Horizontal displacements as small as 0.2 to 0.3 m are accurately measured by optical image correlation at a spatial resolution of less than 20 m. Comparisons with field survey measurements of horizontal displacement are favorable, but some differences are observed due to the different spatial scales of the measurements. Liquefaction-induced horizontal displacements derived from LIDAR surveys are similar to those from optical image correlation, but in some locations the LIDAR measurements are inaccurate due to limitations in the LIDAR survey acquisition methodology used. This paper demonstrates that optical image correlation from satellite image pairs can be used to create more complete databases of liquefaction-induced horizontal movements, which can be used to improve current predictive models for liquefaction-induced horizontal displacements. Future post-earthquake investigations and research should make use of optical image correlation to document the horizontal displacements associated with liquefaction.